2007
DOI: 10.3174/ajnr.a0497
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Combined Intracranial Thrombolysis and Carotid Stenting in the Hyperacute Management of Stroke Patients with Severe Cervical Carotid Stenosis

Abstract: BACKGROUND AND PURPOSE:The timely re-establishment of intracranial perfusion, the effective prevention of early recurrent strokes, and the limitation of the incidence of reperfusion injury are the major factors that are key to successful treatment of patients with hyperacute stroke who had severe ipsilateral cervical internal carotid artery (ICA) stenosis. In an effort to reduce both the extent of the ongoing neurologic injury and the risk of early recurrent stroke, we have adopted an aggressive combined endov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…The main focus of previous studies has been the procedure itself and short-term clinical results; information regarding follow-up vascular investigations has been reported in only four studies 4 5 9 10. Of the patients included in these studies, only one showed asymptomatic moderate stenosis of approximately 40% 5.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of previous studies has been the procedure itself and short-term clinical results; information regarding follow-up vascular investigations has been reported in only four studies 4 5 9 10. Of the patients included in these studies, only one showed asymptomatic moderate stenosis of approximately 40% 5.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Several of these studies show that endovascular therapy appears to convey a benefit over IV-tPA alone in acute strokes involving the ICA. 8,10,11 With the advent of endovascular therapy used in combination with IV-tPA, the careful preselection of suitable patients is crucial in maximizing clinical outcomes. Our study findings propose important factors to consider in selecting extracranial ICA occlusion patients for revascularization treatment using IV-tPA.…”
Section: Article In Pressmentioning
confidence: 99%
“…[7][8][9] Only few studies have focused on the response to IV-tPA in patients with primary acute occlusion of cervical ICA. [10][11][12] These disparate populations may have different hemodynamic properties and response to IV-tPA. 8 We identified AIS patients with primary occlusion of cervical ICA from our thrombolysis cohort and analyzed them for the determinants of functional outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies have reported CAS as effective for symptomatic carotid stenosis 1) . Additionally, the number of studies reporting the effectiveness and safety of CAS for AIS are growing 19,27,41,44) . However, the evidence supporting CAS for AIS was not established in the 2018 guideline.…”
Section: And Cerebral Artery Stenosismentioning
confidence: 99%